Management Proposal for the Adoption of BIM in Manufacturing Companies - Guzmán Flores, Alex Mauricio (2023)
The adoption of BIM in the construction sector has generated in project designers the need for precise, reliable and detailed information about the components that they will use in their models, and the manufacturers of these components can provide this information through object catalogs BIM. By providing this information, designers are more likely to use your products in projects that apply this methodology, leading to more business opportunities. This article proposes a management model to implement BIM in manufacturing companies, which considers the recommendations made by the Project Management Institute (PMI) in its Guide to the Fundamentals for Project Management, and also proposes a standard for the creation of BIM objects that allow their interoperability and guarantee the quality of the information in a BIM catalogue.